2004
DOI: 10.1021/ic049820t
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and Magnetic Behavior of the Ln Derivatives (Ln = Nd, La) of a 2,6-Diiminepyridine Ligand and Corresponding Dianion

Abstract: An unprecedented Nd[2,6-[[2,6-(i-Pr)(2)C(6)H(5)]N=C(CH(3))](2)(C(5)H(3)N)]NdI(2)(THF) (1) complex was prepared by oxidizing metallic Nd with I(2) in THF and in the presence of 2,6-[[2,6-(i-Pr)(2)C(6)H(5)]N=C(CH(3))](2)(C(5)H(3)N). The magnetic behavior at variable T clearly indicated that the complex should be regarded as a trivalent Nd atom antiferromagnetically coupled to a radical anion. By using the doubly deprotonated form of the diimino pyridine ligand [[2,6-[[2,6-(i-Pr)(2)C(6)H(5)]N-C=CH(2)](2)(C(5)H(3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 38 publications
5
64
0
2
Order By: Relevance
“…As usual, the distance between Cl and rare earth elements is 2.50–3.00 Å . In this complex, the La–Cl distances are 2.948(33) Å and 2.958(36) Å, it is very similar with those reported in the literature . The La–O distances are in the range of 2.449(72)–2.616(51) Å and La ··· La distances are approximately 4.060(10) Å .…”
Section: Resultssupporting
confidence: 87%
“…As usual, the distance between Cl and rare earth elements is 2.50–3.00 Å . In this complex, the La–Cl distances are 2.948(33) Å and 2.958(36) Å, it is very similar with those reported in the literature . The La–O distances are in the range of 2.449(72)–2.616(51) Å and La ··· La distances are approximately 4.060(10) Å .…”
Section: Resultssupporting
confidence: 87%
“…The ability of bis(imino)pyridines to undergo a broad range of chemistries in their own right such as deprotonation [80,81,82,83] , alkylation [82,83,84,85,86,87,88] and reduction [89,90] has been the subject of numerous reports and has been reviewed elsewhere [13,14,91] .…”
Section: Ligand Preparationmentioning
confidence: 99%
“…While redox-active ligands have been proven to impart interesting magnetic [8,9] or electrochemical [10][11][12] properties to the rare earth elements due to their ability to stabilize ligand radicals, [13,14] fewer examples exist that demonstrate productive electron movement for new bond formation. Mazzanti et al reported tetradentate Schiff base complexes of Nd, Eu, Tb,Ybthat, upon reduction, store two electrons in anew CÀC s bond.…”
mentioning
confidence: 99%